Gen Z and Podcasts: What They’re Listening to and Why in the Digital Age: A Uses and Gratifications Theory Approach - M, Venkatesh; M, Sripriya (South India Journal of Social Sciences, 2026)
This study investigates the motivations and preferences of Generation Z (Gen Z) podcast listeners in India through the theoretical lens of the Uses and Gratifications Theory (UGT). As a digitally native cohort, Gen Z is driving the exponential growth of the Indian podcast market, yet research into their specific consumption patterns, particularly in non-Western contexts, remains limited. This paper addresses this gap by employing a mixed-methods research design, combining quantitative survey data from 250 Gen Z respondents in Coimbatore, Tamil Nadu, with qualitative insights from 30 semi-structured interviews. The findings reveal that the primary gratifications sought by this demographic are entertainment (M=4.5/5) and escapism (M=4.2/5), which significantly predict preferences for comedy and lo-fi genres, respectively. Spotify and YouTube emerge as the dominant platforms, with a notable trend towards video-integrated podcasts. The study confirms that podcasts are favored over traditional media like radio due to their on-demand nature and flexibility, aligning with Gen Z's multitasking lifestyles. Thematic analysis of qualitative data highlights podcasts' role in providing comfort from digital overload and fostering parasocial connections. This research contributes to the application of UGT in a digital, cross-cultural context and offers practical implications for content creators, marketers, and educators seeking to engage with this influential consumer group. The findings underscore the need for authentic; niche content distributed via social media and influencer channels to effectively reach the Indian Gen Z audience.